Pelatihan Pembuatan dan Penerapan Pompa Tanpa Motor (Hydraulic Ram Pump) untuk Membantu Irigasi Areal Pertanian Masyarakat Petani di Dusun Curup Desa Banjar Negeri Kabupaten Pesawaran - Sinaga, Jorfri Boike; Suudi, Ahmad; Yonanda, Ahmad; Sinaga, David; Effendi, M. Fadhly; Sagala, Surya Jonathan (Nemui Nyimah, 2025)
This paper presents training activities on the construction of a hydraulic ram pump were provided to the farming community of Dusun Curup, Gedong Tataan District. The training material included both theoretical and practical aspects, covering the principles of hydraulic ram pump operation, material selection, construction of the hydraulic ram pump, installation and operation in the field, and maintenance of the pump. The community's enthusiasm for participating in this training was very good, as they sought to understand the construction of the hydraulic ram pump. This can be seen from the community's serious attitude and the many questions they asked during the theoretical and practical sessions on the construction of the hydraulic ram pump. The results of this activity also increased the community's desire to apply the use of this pump to assist with their agricultural irrigation, utilizing village funds, while still requesting guidance from the implementation team of the Mechanical Engineering Deparment at the University of Lampung